CRITERIA TO CONSIDER PRIOR TO A LIGHTING DESIGN OF A CLASSROOM: CLASSROOMS IN CONSTANTINE AS THE FIELD OF PARTICULAR INTEREST (Sciences & Technology. A, exactes sciences, 2000)
This paper is an introductory section of a more detailed research work, which concern the elaboration of basic guidance for lighting design in local primary school classrooms. Its objective is to discuss the criteria a designer should consider before establishing a lighting design project. This is achieved through an investigation of the visual performance of the tasks undertaken. Where the visual task is critical, it is necessary to attribute more importance to the activities to take place instead of the enclosure itself, which means to the functional lighting.